A Short Review on Copper Calcium Titanate (CCTO) Electroceramic: Synthesis, Dielectric Properties, Film Deposition, and Sensing Application - Ahmadipour, Mohsen; Ain, Mohd Fadzil; Ahmad, Zainal Arifin (Nano-Micro Letters, 2016)
Electroceramic calcium copper titanates (CaCu3Ti4O12, CCTO), with high dielectric permittivities (ε) of approximately 105 and 104, respectively, for single crystal and bulk materials, are produced for a number of well-established and emerging applications such as resonator, capacitor, and sensor. These applications take advantage of the unique properties achieved through the structure and properties of CCTO. This review comprehensively focuses on the primary processing routes, effect of impurity, dielectric permittivity, and deposition technique used for the processing of electroceramics along with their chemical composition and micro and nanostructures. Emphasis is given to versatile and basic approaches that allow one to control the microstructural features that ultimately determine the properties of the CCTO ceramic. Despite the intensive research in this area, none of the studies available in the literature provides all the possible relevant information about CCTO fabrication, structure, the factors influencing its dielectric properties, CCTO immobilization, and sensing applications.